PERSPEKTIF ORANG TUA TERHADAP KEMAMPUAN BACA TULIS ANAK SEBELUM MEMASUKI SEKOLAH DASAR - Dewiyana, Safa Putri; Herianingtyas, Nur Luthfi Rizqa (LPPM Universitas Bina Bangsa, 2023)
This research was conducted with the aim of describing the views of parents on children's literacy abilities before entering elementary education. Parents are worried about their children's ability to keep up with school, especially when preparing them to start elementary school (SD). This concern is reflected from various perspectives in society. To change this perspective, support from the government is needed, such as changing the requirements for admitting new students to elementary schools. Thus, it is expected to reduce misunderstandings and high expectations from parents for their children's learning achievements. This study uses a descriptive qualitative approach as the main approach to achieve the research objectives. The necessary data is collected through online observation using a Google form. The results of this study include: (1) parents' views, (2) stages of language development in early childhood, (3) early childhood reading ability, (4) early childhood writing ability, (5) the role of parents in developing interest reading and writing for early childhood, and (6) the obstacles encountered in developing early childhood interest in reading